Pengambilan Keputusan Berdasarkan Fakta dalam Sistem Manajemen Mutu di Sekolah - Wijiati, Luluk; Sari, Yunita; Ningrum, Ike Kusuma; Azainil, Azainil; Komariyah, Laili (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Fact-based decision making is an essential element in the implementation of quality management systems in schools. This approach emphasizes the importance of using accurate, relevant, and accountable data in every decision-making process related to planning, implementation, evaluation, and improvement of educational quality. In the context of quality management, decisions made objectively based on facts can enhance program effectiveness, resource efficiency, and the trust of all school stakeholders. This study aims to provide a deeper explanation of fact-based decision making. The research method used is a literature review, which seeks foundational sources to build theoretical frameworks, conceptual thinking, and hypotheses. The results show that several approaches have been developed by experts to integrate data into the decision-making process. There are several key aspects to consider in fact-based decision making according to various experts. Strategies in decision making include structured approaches to quantitative and qualitative data analysis, as well as collaborative and participatory approaches. Techniques used in decision making include Root Cause Analysis (RCA), Fishbone Diagram, and SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats).